Zambia : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses implementation of the Fifth National Development Plan (FNDP) in Zambia. The planning process of the FNDP integrated views from the Provincial and District Development Plans approved by the respective provincial and district level organs. The FNDP's goals are multipronged. The government recognizes that wealth creation through sustained economic growth constitutes the most important element in poverty reduction and, consequently, a high premium is being placed on growth-stimulating interventions. The government also recognizes that redistributive policies do matter for reducing poverty and that growth and equity are not necessarily in conflict.